2018
DOI: 10.1016/j.ijsu.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Is sharing speaker's slides from conference presentations on social media a breach of intellectual property or a delegate's right? Depends who you ask

Abstract: Contemporary opinion regarding this subject differs depending on the modality of questionnaire and population interrogated. Respondents who use social media in their professional practice are more comfortable with the practice of sharing speaker's slides. Whilst, the sharing of speaker's slides is legal in Europe, but it may be good practice to seek consent and acknowledge the author in any communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Twitter is also widely adopted in the United States, but primarily utilized for promotional content rather than educational [ 11 ]. Previous research on hernia surgeons demonstrated that those who use #SoMe in their professional practice are more interested in sharing the speakers’ slides on #SoMe at conferences [ 12 ]. Mayol et al described the potential contributions of #SoMe to surgical research, including widening of international networks and keeping up to date with evolving surgical techniques [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Twitter is also widely adopted in the United States, but primarily utilized for promotional content rather than educational [ 11 ]. Previous research on hernia surgeons demonstrated that those who use #SoMe in their professional practice are more interested in sharing the speakers’ slides on #SoMe at conferences [ 12 ]. Mayol et al described the potential contributions of #SoMe to surgical research, including widening of international networks and keeping up to date with evolving surgical techniques [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…One has to keep in mind that social media is not peer-reviewed nor curated, and, thus, liable to some types of negative influences. Not all may be willing to share their slides, preliminary data or outcomes on social media [18], thus a policy of steps forward with opportunities and considerations to threats may be useful to issue for users. Useful steps and tips from other stakeholders are already available and should be implemented in a structured fashion [1].…”
Section: Discussionmentioning
confidence: 99%
“…Исследования показали, что большинство докладчиков довольны тем, что содержание их докладов распространяется другими врачами [19]. Тем не менее право ограничить это распространение остается как за докладчиками, так и за организаторами конференции [20,21].…”
Section: проблемы и противоречия связанные с распространением содержа...unclassified